History of PPE : special reference to beaked masks during the black death and its aftermath - Puteh Noraihan A Rahman; Alexander Kam; Arina Azmi; Zasra, Radias (Penerbit Universiti Kebangsaan Malaysia, 2022)
The background of the research will focus on the cases of the Black Death pandemic in 14th century onwards with particular review on the usage of beaked masks by plague doctors. This peculiar mask can be described as Personal Protective Equipment (PPE) at that time to protect the physicians from being infected when treating patients with Black Death symptoms. This research will evaluate the use of PPE from the medical, history, chemistry, technology and sociology perspectives to reach a detailed understanding of the benefits of wearing this peculiar mask in responding to the challenges presented by the epidemic. Hence, the ingredients and elements of the beaked masks need to be scrutinized in order to underscore the physicians’ efforts in inventing such equipment in protecting frontline workers like the plague doctors. Analyzing the evolution of PPE and medical protection will help the public to understand medical history and the roles of community in dealing with cataclysmic epidemics in the past. The research found that beaked masks created as PPE by the physicians were able to support them psychologically in dealing with their patients. Unfortunately, the design and property inside beaked masks do not provide the expected protection unlike PPE in modern time which produced significant result in reducing the possibility of disease transmission.